1968
DOI: 10.1002/pol.1968.150060503
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic polydiketopiperazines

Abstract: Aromatic polydiketopiperazines have been prepared from bis‐2‐chloroacetamides of aromatic diamines in the presence of an epoxide as HCl acceptor and a quaternary ammonium halide catalyst. The structures of the polymers were characterized by infrared and NMR spectra. These polymers were soluble in organic acids such as formic acid, dichloroacetic acid, and trifluoroacetic acid but insoluble in common organic solvents such as dimethylformamide, dimethylacetamide, and dimethyl sulfoxide. Thermogravimetric analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1968
1968
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…These polymers present a number of attractives both from a practical and a purely scientific standpoint. To our knowledge the only reports which have appeared in the literature on polymers containing diketopiperazine rings in the main chain are those of KOBAYASHY et al2) and IWAKURA et al 3). These authors worked, however, under experimental conditions quite different from ours.…”
Section: Introductionmentioning
confidence: 99%
“…These polymers present a number of attractives both from a practical and a purely scientific standpoint. To our knowledge the only reports which have appeared in the literature on polymers containing diketopiperazine rings in the main chain are those of KOBAYASHY et al2) and IWAKURA et al 3). These authors worked, however, under experimental conditions quite different from ours.…”
Section: Introductionmentioning
confidence: 99%
“…Crescenzi et al [12,13] and Iwakura et al [14] obtained polyamides from L-lysine Summary: Reaction of active esters of O-protected D-and L-tartaric acid with L-lysine 2,5-diketopiperazine afforded optically active low molecular weight compounds with T g % 130 8C. 13 C NMR results indicated that the condensation product consisted of cyclic oligomers made from 1 to 6 repeating units.…”
Section: Introductionmentioning
confidence: 99%
“…The polymerization of DKPs has been reported in the literature. Iwakura et al9 produced a heat‐stable plastic that also contained phenyl rings and decomposed between 400 and 500 °C. Kobayashi et al10 reported that melt‐spun fibers formed from DKP–amine resins had a strength of 3.2 g/denier and were dyeable.…”
Section: Introductionmentioning
confidence: 99%